Students' Continuance Intention to Use LMS in Higher Education: A Technology Acceptance Model Study - Fitria; Abdul Hafid Hasim (Yayasan pendidikan dzurriyatul Quran, 2026)
Digital learning sustainability in higher education depends not only on the availability of a Learning Management System (LMS), but also on students' willingness to continue using it as a meaningful learning environment. This study aims to examine how perceived ease of use and perceived usefulness influence students' continuance intention to use an LMS within a higher education context. A quantitative survey was conducted with 120 university students who had direct experience using an LMS for course materials, assignment submission, academic communication, and learning management. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The measurement model met validity and reliability criteria, with loading factors above 0.70, AVE values above 0.50, and Cronbach's Alpha and Composite Reliability values above 0.70. The structural model shows that perceived ease of use significantly affects perceived usefulness (beta = 0.684; p < 0.001) and continuance intention to use (beta = 0.312; p = 0.004). Perceived usefulness also positively affects continuance intention to use (beta = 0.547; p < 0.001). Together, perceived ease of use and perceived usefulness explain 61.8% of the variance in continuance intention. The findings imply that LMS sustainability in higher education requires user-friendly design and clear pedagogical value.